2004
DOI: 10.1086/380130
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Severe Liver Fibrosis in Human Immunodeficiency Virus–Infected Patients with Chronic Hepatitis C: A European Collaborative Study

Abstract: A study was performed in 10 European health care centers in which 914 patients coinfected with hepatitis C virus (HCV) and human immunodeficiency virus (HIV) who had elevated serum alanine aminotransferase (ALT) levels underwent liver biopsy during the period of 1992 through 2002. Overall, the METAVIR liver fibrosis stage was F0 in 10% of patients, F1 in 33%, F2 in 22%, F3 in 22%, and F4 in 13%. Predictors of severe liver fibrosis (METAVIR stage, F3 or F4) in multivariate analysis were age of >35 years (odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
160
3
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(185 citation statements)
references
References 32 publications
14
160
3
8
Order By: Relevance
“…It has been shown that the immune restoration associated with ART can limit the progression of HCV-associated disease so that even if they do not respond to HCV therapy there may be some longterm indirect benefit from ART [172,[197][198][199].…”
Section: General Principles Of Anti-hcv Therapymentioning
confidence: 99%
“…It has been shown that the immune restoration associated with ART can limit the progression of HCV-associated disease so that even if they do not respond to HCV therapy there may be some longterm indirect benefit from ART [172,[197][198][199].…”
Section: General Principles Of Anti-hcv Therapymentioning
confidence: 99%
“…5 Most data on liver fibrosis progression in HIV and HCV coinfection come from cross-sectional studies that relied on a single liver biopsy. [6][7][8][9][10][11] In those studies, the date of HCV infection is usually estimated as the date of the first use of injection drugs. At HCV infection, it is assumed that liver fibrosis is absent.…”
mentioning
confidence: 99%
“…These assumptions are probably one reason for the conflicting results of those studies, especially regarding the effect of ART on fibrosis progression. [6][7][8][9][10][11] Serial liver biopsy studies may have some advantages over single liver biopsy studies. Changes in fibrosis stage are observed between two dates, and fibrosis at the initial date is known.…”
mentioning
confidence: 99%
“…Progression of hepatic fibrosis has been associated in HCV/HIV co-infected patients with some factors like gender (males), more advanced age when HCV infected, higher alcohol ingestion, lymphocytes CD 4 + cells < 500/mm 3 and HAART non-users [14,15]. In mono-infected patients, iron overload and hepatic steatosis may also be associated with a rapid fibrotic progression [16,17].…”
Section: It Is Known That Human Immunodeficiency Virus (Hiv) May Modimentioning
confidence: 99%